Experimental and computational investigations of 2-amino-6-bromobenzothiazole as a corrosion inhibitor for copper in sulfuric acid. Issue 19 (2nd October 2018) - Chen, Jie; Qiang, Yujie; Peng, Shini; Gong, Zhili; Zhang, Shengtao; Gao, Lanzhou; Tan, Bochuan; Chen, Shijin; Guo, Lei
Abstract: 2-amino-6-bromobenzothiazole (ABBT) as an inhibitor of copper corrosion in 0.5 M H2 SO4 solution was researched in this study using with electrochemical measurement, scanning electron microscope, atomic force microscope, and theoretical calculation. Polarization curves manifest that ABBT acts as a modest cathodic-type inhibitor with a maximum achievable inhibition efficiency of 94.6% at 1 mM. EIS test indicates that ABBT adsorb on the copper surface and form an adsorption film, which obeys Langmuir adsorption model. Furthermore, DFT calculation and molecular dynamics simulation were utilized to explore the mechanism of inhibition of ABBT.